Statistical analysis of the factors of information society development in the Russian Federation - G. P. Sorokina; T. A. Pershina; E. A. Dolgikh (Вестник университета)
The article summarises the system of indicators characterising the development of the information society. A generalising characteristic of the subjects of the Russian Federation was given for each of the 23 indicators, which made it possible to identify regions with different fluctuations of the trait. All indicators have been formed into four factors: human capital, innovation potential, information and communication infrastructure and access, and the economic environment. According to the indicators included in each group, the corresponding subindexes have been calculated. Ratings of regions according to the value of sub-indices have been compiled. Based on the values of the sub-indices, the integral indicator characterising the development of the information society has been calculated. The leading and lagging subjects of the Russian Federation in terms of its significance have been identified. In order to identify regions that are homogeneous in terms of the level of development of the information society, their grouping has been carried out.